Enhanced recovery after surgery program alleviates neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in patients undergoing gynecological surgery - Xing, Naidong; Wang, Hongyan; Huang, Yan; Peng, Jin (Frontiers in Medicine, 2023)
ABSTRACT Background: To evaluate the efficacy of the enhanced recovery after surgery (ERAS) programs on the systemic inflammatory response (SIR) of patients following gynecological surgery, a randomized controlled trial is performed to compare ERAS programs with the conventional perioperative care programs. Furthermore, the novel SIR markers could be identified to evaluate ERAS programs of gynecological surgery. Methods: Patients undergoing gynecological surgery were randomly allocated to either the ERAS group or the conventional group. The correlations between the elements of ERAS protocols and SIR markers following gynecological surgery were evaluated. Results: 340 patients indicated for gynecological surgery were enrolled (ERAS=170, conventional=170). We firstly identified that ERAS programs reduced the perioperative difference of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) induced by gynecological surgery. Interestingly, first flatus time postoperatively, visual analogue scale (VAS) score of patients was positively related with perioperative difference of NLR, PLR. Moreover, we discovered that perioperative difference of NLR, PLR was correlated with elements of ERAS protocol, including first sips of water, first semifluid diet postoperatively, pelvic drain duration, out of bed time of patients. Conclusions: We originally reveal that certain elements of ERAS programs alleviated SIR to operation. The implementation of ERAS programs enhances postoperative recovery after gynecological surgery via improving system inflammatory status. NLR or PLR could be the novel and inexpensive marker to assess ERAS programs in gynecological surgery.